Assessing knowledge, attitude, and practice of emergency contraception: a cross- sectional study among Ethiopian undergraduate female students - Ahmed Fatuma A; Moussa Kontie M; Petterson Karen O; Asamoah Benedict O (BMC, 2012)
Abstract Background Emergency contraception (EC) is a type of modern contraception which is indicated after unprotected sexual intercourse when regular contraception is not in use. The importance of EC is evident in preventing unintended pregnancies and its ill consequences like unintended child delivery or unsafe abortion, which are the most common causes of maternal mortality. Therefore, EC need to be available and used appropriately as a backup in case regular contraception is not used, misused or failed. Knowing that Ethiopia is one of the countries with highest maternal mortality rate, this study aimed to assess the knowledge, attitude and practice of EC, and to further elucidate the relationship between these factors and some socioeconomic and demographic characteristics among female undergraduate students of Addis Ababa University (AAU). This information will contribute substantially to interventions intended to combat maternal mortality. Methods A Cross-sectional quantitative study among 368 AAU undergraduate students was conducted using self-administered questionnaire. Study participants were selected by stratified random sampling. Data was entered and analyzed using SPSS Version 17. Results were presented using descriptive statistics, cross-tabulation and logistic regression. Results Among the total participants (n = 368), only 23.4% were sexually active. Majority (84.2%) had heard of EC; 32.3% had a positive attitude towards it. The main source of information reported by the respondents was Media (69.3%). Among those who were sexually active, about 42% had unprotected sexual intercourse. Among those who had unprotected sexual intercourse, 75% had ever used EC. Sexually active participants had significantly better attitude towards EC than sexually inactive participants (crude OR 0.33(0.15-0.71)); even after adjusting for possible confounders such as age, region, religion, ethnicity, marital status, department and family education and income (adj. OR 0.36(0.15-0.86)). Conclusions The study showed high EC awareness and usage in contrast to other studies in the city, which could be due to the fact that university students are relatively in a better educational level. Therefore, it is highly recommended that interventions intended to combat maternal mortality through contraceptive usage need to be aware of such information specific to the target groups.